OR Forum—The Cost of Latency in High-Frequency Trading - Moallemi, Ciamac C.; Sağlam, Mehmet (Operations Research, 2013)
Modern electronic markets have been characterized by a relentless drive toward faster decision making. Significant technological investments have led to dramatic improvements in latency, the delay between a trading decision and the resulting trade execution. We describe a theoretical model for the quantitative valuation of latency. Our model measures the trading frictions created by the presence of latency, by considering the optimal execution problem of a representative investor. Via a dynamic programming analysis, our model provides a closed-form expression for the cost of latency in terms of well-known parameters of the underlying asset. We implement our model by estimating the latency cost incurred by trading on a human time scale. Examining NYSE common stocks from 1995 to 2005 shows that median latency cost across our sample roughly tripled during this time period. Furthermore, using the same data set, we compute a measure of implied latency and conclude that the median implied latency decreased by approximately two orders of magnitude. Empirically calibrated, our model suggests that the reduction in cost achieved by going from trading on a human time scale to a low latency time scale is comparable with other execution costs faced by the most cost efficient institutional investors, and it is consistent with the rents that are extracted by ultra-low latency agents, such as providers of automated execution services or high frequency traders.